ANALISIS PENGARUH DAYA TARIK IKLAN DAN KEKUATAN CELEBRITY ENDORSER TERHADAP BRAND AWARENESS DAN DAMPAKNYA TERHADAP BRAND ATTITUDE HANDPHONE NOKIA ( Studi Kasus pada Mahasiswa dan Mahasiswi Fakultas Ekonomika dan Bisnis Universitas Diponegoro Semaran - Aji Nugroho, Septiyo; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2013)
Nokia mobile phone as one of the products in Indonesia at first to be a market leader mobile product. Increasing number of mobile products that appear in Indonesia makes the level of competition in mobile products is high, making the level of product sales decreased Nokia. The problem in this research are : advertising effect to brand awareness Nokia mobile phone, the power of celebrity endorser effect to brand awareness Nokia mobile phone, brand awareness has effect brand attitude Nokia mobile phone This research involves 100 college student as its respondent using accidental sampling method. Analyzes it with double-regression linear analysis (t-test and f-test) by SPSS software. The result of regression test shows that advertising has no positive effect to brand awareness, the power of celebrity endorser has positive effect to brand awareness. Brand awareness has no positive effect to brand attitude. The result of F-test show that advertising, the power of celebrity endorser together has positive effect to brand awareness